Aplicación del aula multimedia en el área de lengua y literatura en la carrera de educación básica en La Universidad Técnica De Cotopaxi en el periodo académico 2011-2012 - Venegas Reyes, Daysi Alejandra (2012)
With the application of multimedia classroom in the language and literature area it’s necessary all the resources to Education that includes the entire contents and the structure defined in thematic units for each course, including, in addition to theoretical aspects, interactive exercises and an activity about knowledge self-assessment. Students may access through this project to further reading and other supplements to encourage reading audio files highlighting the stories and historical narratives as well as the videos section of educational dialogues, using video, audio and pictures of educational interest.